Kausalitas Pertumbuhan Ekonomi Daerah, Suku Bunga, dan Permintaan-Penawaran Kredit: Pemodelan Simultan - Suriani, Suriani; Seftarita, Chenny (Jurnal Samudra Ekonomi dan Bisnis, 2022)
This study analyzes the effect of regional economic growth and interest rates on the demand-supply of credit in Aceh Province. The initial objective of the reduction regression is to analyze the effect of loan to deposit ratios, non-performing loans, loan to value, and interest rates on regional economic growth and the final stage is to investigate the causal relationship between regional economic growth and total loans disbursed in Aceh Province. The data period used is 2011-2014 quarterly. The method used was two-stage least square regression. The regression results indicate that regional economic growth has a positive effect on bank lending. However, interest rates do not affect total lending. The results of the causality test explain that regional economic growth has a causal relationship with credit disbursement. The local governments can improve the regional economy by supporting productive economic funding through banking financial institutions.